Anxiety in science learning - Ahmad, Mohd Khairul Azmi; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Anxiety is a phenomenon which occurs when the person faces a threatening situation. It is a negative multifaceted feeling (emotion, cognitive, somatic and behavioural) which can be categorized into two types; state anxiety and trait anxiety. In the modern society, there are generally several forms of anxiety such as math anxiety, social anxiety, sport anxiety, computer anxiety, test anxiety, terror related and trauma. Many factors are contributing to the excellence of student learning; specifically, in science including science anxiety. Science anxiety refer to the students’ uneasiness feeling on learning science compared to the nonscience subjects. This concept was introduced by Mallow since 1977 through the Science Anxiety Clinic at Loyola University, Chicago. Previous studies found science anxiety increases, the academic performance of students will be degraded. It is influenced by gender which is more affects female students.